POLA PERESEPAN ANTIBIOTIK PROFILAKSIS PRE BEDAH SECTIO CAESAREA DI RUMAH SAKIT - Saleh, Chusun; Kurniasari, Maya (Jurnal Riset Kefarmasian Indonesia, 2021)
Caesarean section is a surgery to give birth to a child through surgery on the abdominal wall and uterus. Prophylactic antibiotics are preventive antibiotics in Sectio Caesarean surgery. This study aims to determine the pattern of prescribing prophylactic antibiotics in preoperative caesarean section patients which are grouped into 4 specific objectives, namely: patient characteristics such as (age, parity status, payment status), antibiotic class, type of antibiotic, and to determine surgical wound indication ILO, This study used a descriptive method by retrospectively taking data by looking at the prescription (e-prescription), patient medical record data and SOAP (Subjective, Objective, Assessment, Planning). The results showed that out of 300 patients who were parturient, 52 patients (17.3%) had normal delivery and 248 patients with caesarean delivery (82.7%). Most of the ages were between 20-30 years as many as 123 patients (49.6%) and aged > 30-40 years as many as 120 patients (48.38%). As for the status of the most payments in cash, namely 176 patients (71%). The most frequently used antibiotic class is the Cephalosporin group, namely 246 patients (99.6%), the most commonly used type of antibiotic is Ceftriaxon, which is 175 patients (70.6%). The study on Surgical Wound Infection was found in only 1 patient (0,4%) with the antibiotic Ceftriaxon.